Factors affecting local leaders’ perception on the adaptation ability of Malaysian small scale fishermen towards climate change - Man, Norsida; Sahharudin, Nor Farhana; Abu Samah, Asnarulkhadi; Mohamed Shaffril, Hayrol Azril (Human Resource Management Academic Research Society, 2017)
Background: Early Childhood Caries (ECC) refers to rampant dental caries in pre-school children. It can affect the child both physically and psychologically. Many factors can affect knowledge and attitude of mothers regarding preventing ECC. The objective is to study the knowledge and attitude of the associated factors of ECC of Arabic mothers of preschool and primary school children in Arabic schools that are registered in the Ministry of Education in Klang Valley in Malaysia. Materials and Methods: A cross sectional study was conducted among 518 Arabic children’s mothers using validated and reliable questionnaire. Simple random technique was used. Data was analysed by using Chi-square and logistic regression. Result: Level of good knowledge on ECC was 49.1% and positive attitude level was 46.6%. The predictors of good knowledge on ECC were respondents with > 4 children (AOR=3.386; 95% CI: 1.779-6.447), have no fears originating from community believes (AOR=1.575; 95% CI: 1.000-2.480), have no fears of extraction (AOR=2.845; 95% CI: 1.443-5.608), and brush twice daily (AOR=1.989; 95% CI: 1.266-3.126). Predictors of positive attitude were respondents with post graduate level (AOR=2.024; 95% CI: 1.287-3.184), attended education program (AOR=2.444; 95% CI: 1.325- 4.506), and have good knowledge level (AOR=2.479; 95% CI: 1.600-3.843). No fears originating from community believe was a protective factor (AOR=0.575; 95% CI: 0.369-0.896). Conclusion: Preventive programs should target vulnerable mothers who are 35 years old or less, have bachelor degree or less, have four children or less, haven’t attended any infant oral health education program and have dental fears.